“Percepciones de los estudiantes de comunicación social de la Universidad Técnica de Cotopaxi para la promoción audiovisual del patrimonio material inmueble de Latacunga” - Bedoya Sánchez, Janis Carolina (2020)
The objective of this research was to identify the perceptions of the students of the seventh cycle of Universidad Técnica del Cotopaxi Social Communication career about the audiovisual promotion of the real estate material patrimony of the historic center of Latacunga city. The project started from a theoretical reference in which definition of cultural heritage, audiovisual promotion, perception, historical center among others, were given. They provided valuable conceptual clarifications. Then, the historic center of Latacunga was studied, concentrating on the description of some icons of both, material and religious real estate legacy. It was emphasized the knowledge of the symbolic value of each building. The research carried out is descriptive, explanatory and purposeful with a qualitative approach. Two techniques were used, the first a focus group, where the perceptions and interests of the students on the designing of audiovisuals for the promotion of cultural heritage was distinguished. And the second was an interview that contributed with historical information of the buildings of the historical center of the city, as well as interesting socio-cultural assessments of heritage. To support this proposal, we produced an audiovisual demonstration, titled “Touring the historic center of Latacunga”, which has the purpose of boosting and promoting the care, maintenance and preservation of cultural heritage in the citizenship.